KEWENANGAN BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) KABUPATEN/KOTA DALAM PENYELESAIAN SENGKETA PROSES PEMILIHAN UMUM DI LOMBOK TENGAH PADA PEMILIHAN UMUM TAHUN 2019 - AWALUDIN, AWALUDIN; GERHAN, ANTHONI; SUHERMAN, SUHERMAN; UTAMA, LALU NUGRAHA ADI (GANEC SWARA, 2024)
Bawaslu Decision number 02/PTS/PSPP/BWSL.LTH.18.06/IX/2018 in the 2019 Election accommodates the right of former corrupt convicts to nominate themselves as legislators. Meanwhile, the regulations issued by the KPU through PKPU number 20 of 2018 prohibit corrupt convicts from becoming legislative candidates. Regency/city Bawaslu, with its quasi-judicial authority, in deciding a dispute, its decision can annul the KPU's decision or the dispute's decision is contrary to the norms regulated in the PKPU. The aim of this research is to determine the implementation of the Regency/City Bawaslu's authority in resolving election process disputes in the Central Lombok Regency Bawaslu in the 2019 Election. The authors used empirical legal research methods. Decisions issued by Bawaslu have a juridical character similar to the strength of decisions resulting from the litigation process in court. However, what is different is that Bawaslu decisions are final and binding for process disputes between election participants, whereas for process disputes between election participants and election organizers, some are binding and some are non-binding for several types of decisions, so there are other legal remedies that can be taken by The Parties are taking legal action at the State Administrative Court (PTUN)